Strategic legal imperatives for directors to consider the context of legalised substance industries: identifying potential future challenges for Psilocybin businesses in South Africa though a comparative study of Cannabis Regulation in the USA, Canada and the Netherlands - Fiebig, Fiona (Department of Commercial Law, 2024)
Psilocybin is a chemical compound found in various species of Psilocybe mushrooms and is currently classified as an illegal drug. There is, however, growing advocacy for the decriminalisation and/or legalisation of psilocybin due to its well-documented medical benefits. Therefore, it is pertinent to discuss specific duties directors will have to pay attention to in evolving legalised substance industries such as psilocybin, so they can effectively discharge their duties and successfully navigate this underregulated industry. There is currently little legal research on psilocybin, however; proponents of its legalisation appear to be adopting policies from the cannabis sector to widen access to psilocybin. This thesis bases its analysis and conclusions on research about cannabis businesses. The United States (US) serves as the best example of the legal issues associated with deregulation and incremental legalisation within legalised substance industries, therefore, the focus of this dissertation is on the current challenges within the US cannabis market and how it relates to the upcoming psilocybin market in South Africa. The literature from the US market is further supplemented by additional information from the Netherlands and Canadian markets. The director's duties discussed herein apply to a wide range of industries, however, this research indicates that conducting business within legalised substance industries creates distinct risks and challenges within the scope of the directors' duties under consideration. It is important to note that due to the current legal status of psilocybin, this research is speculative and creates a standard for psilocybin businesses in future. This paper advances legal research into psilocybin whilst proposing important guidelines for directors in psilocybin businesses, which will allow them to discharge their duties, as well as further good corporate governance within these legalised substance industries.